The introduction of advanced practice physiotherapy within Dutch primary care is a quest for possibilities, added value, and mutual trust: a qualitative study amongst advanced practice physiotherapists and general practitioners - Sylvia Pellekooren; Marianne Donker; Eddy Reijnders; Lamyae Boutalab; Raymond Ostelo; Maurits van Tulder; Annelies Pool-Goudzwaard (BMC, 2022)
Abstract Background Despite the increased deployment and added value of Advanced Practitioner Physiotherapy (APP) in musculoskeletal care internationally, APP is not yet widely accepted within Dutch primary care. This may be due to specific constraints in the implementation of APP within the Dutch healthcare system. This study aimed to explore the experiences and perceptions of Advanced Practitioner Physiotherapists (APPs) and General Practitioners (GPs) with respect to implementing APP within Dutch primary care. Methods This explorative and interpretive qualitative study included 12 APPs and 3 GPs who were in various stages of implementing an APP care model. Semi-structured interviews were conducted between January and March 2021. The topic list was based on existing literature, the personal input of researchers, and the Constellation Approach framework. Data were analysed using a thematic inductive approach. Results Four main themes emerged from the data; 1) Both GPs' trust in APP and a clear added value of APP are critical for starting implementation, 2) APPs need continuous support from GPs, 3) APPs believe that their position needs strengthening, and 4) Implementation of the APP model creates tension over ownership. These four themes highlight the perceived difficulties in gaining trust, lack of clarity over the added value of APP, ambiguity over APPs' professional profile and positioning, a need on behalf of GPs to maintain authority, lack of reimbursement structure, and the struggle APPs face to strike a balance with current care. Conclusion This study demonstrates that implementing an APP model of care is challenging, in part, because the deployment of APP does not sufficiently align with the core values of GPs, while GPs appear reluctant to hand over control of elements of patient care to APPs. APPs do not appear to have ownership over the implementation, given their strong dependence on the practice, values and needs of GPs. Trial registration Ethical approval was obtained from the Medical Ethics Committee of VU University Medical Centre in Amsterdam; reference number 2020.17 . All participants were asked to provide written informed consent prior to participating in the study.